Shape modelling of the oropharynx distinguishes associations with body morphology but not whiplash‐associated disorder. Issue 3 (27th October 2022) - Webb, Alexandra L.; Lynch, Joseph T.; Pickering, Mark R.; Perriman, Diana M.
Abstract: Characterization of the oropharynx, a subdivision of the pharynx between the soft palate and the epiglottis, is limited to simple measurements. Structural changes in the oropharynx in whiplash‐associated disorder (WAD) cohorts have been quantified using two‐dimensional (2D) and three‐dimensional (3D) measures but the results are inconsistent. Statistical shape modelling (SSM) may be a more useful tool for systematically comparing morphometric features between cohorts. This technique has been used to quantify the variability in boney and soft tissue structures, but has not been used to examine a hollow cavity such as the oropharynx. The primary aim of this project was to examine the utility of SSM for comparing the oropharynx between WAD cohorts and control; and WAD severity cohorts. The secondary aim was to determine whether shape is associated with sex, height, weight and neck length. Magnetic resonance (MR) T1‐weighted images were obtained from healthy control ( n = 20), acute WAD ( n = 14) and chronic WAD ( n = 14) participants aged 18–39 years. Demographic, WAD severity (neck disability index) and body morphometry data were collected from each participant. Manual segmentation of the oropharynx was undertaken by blinded researchers between the top of the soft palate and tip of the epiglottis. Digital 3D oropharynx models were constructed from the segmented images and principal component (PC) analysis was performed with the PC weights normalized to z‐scores for consistency. Statistical analyses were undertaken using multivariate linear models. In the first statistical model the independent variable was group (acute WAD, chronic WAD, control); and in the second model the independent variable was WAD severity (recovered/mild, moderate/severe). The covariates for both models included height, weight, average neck length and sex. Shape models were constructed to visualize the effect of perturbing these covariates for each relevant mode. The shape model revealed five modes which explained 90% of the variance: mode 1 explained 59% of the variance and primarily described differences in isometric size of the oropharynx, including elongation; mode 2 (13%) primarily described lateral (width) and AP (depth) dimensions; mode 3 (8%) described retroglossal AP dimension; mode 4 (6%) described lateral dimensions at the retropalatal‐retroglossal junction and mode 5 (4%) described the lateral dimension at the inferior retroglossal region. There was no difference in shape (mode 1 p = 0.52; mode 2 p = 0.96; mode 3 p = 0.07; mode 4 p = 0.54; mode 5 p = 0.74) between control, acute WAD and chronic WAD groups. There were no statistical differences for any mode (mode 1 p = 0.12; mode 2 p = 0.29; mode 3 p = 0.56; mode 4 p = 0.99; mode 5 p = 0.96) between recovered/mild and moderate/severe WAD. Sex was not significant in any of the models but for mode 1 there was a significant association with height ( p = 0.007), mode 2 neck length ( p = 0.044) and in mode 3 weight ( p = 0.027). Although SSM did not detect differences between WAD cohorts, it did detect associations with body morphology indicating that it may be a useful tool for examining differences in the oropharynx. Abstract : Visual summary of the shape variation described by each of the modes of the oropharynx model: Mode 1 described variance in isometric size including elongation; mode 2 width and depth; mode 3 retroglossal antero‐posterior dimension; mode 4 lateral dimensions at the retropalatal and retroglossal junction and mode 5 the lateral dimension at the inferior retroglossal region. Each mode is shown at the limits of ‐2SD and + 2SD from the mean shape.